2020
DOI: 10.1111/rec.13176
|View full text |Cite
|
Sign up to set email alerts
|

Tree shelters facilitate brown oak seedling survival and establishment in a grazing‐dominant forest of Bhutan, Eastern Himalaya

Abstract: Brown oak (Quercus semecarpifolia) forest is essential for ecological and socioeconomic functions, mainly grazing in the Himalayas. The tree has failed to regenerate naturally and is a threatened species. Restoration of brown oaks is crucial to ensure sustainability while maintaining livestock grazing in these habitats. Achieving this requires cost-effective restoration techniques that are practicable and sympathetic to the multiple uses of the forest. We assessed the combined effect of grazing (control) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
4
1
Order By: Relevance
“…Height of N. dombeyi seedlings was not affected by the use of tree shelters neither in the xeric site, and nor in the mesic site, at least until the second growing season (prior to the browsing effect). This result contrasted with those of several hardwood (Davies 1985;Tuley 1985;Gillespie et al 1996;Bendfeldt et al 2001;McCreary and Tecklin 2001;Dorji et al 2020) and conifer species (Ward et al 2000;Jacobs 2011), which had shown a pronounced positive impact on height with the use of tree shelters. It seems that our results agree with those of the authors who indicate that the net effect of tree shelters on plant growth appeared to be site-and/or species-dependent (Frearson and Weiss 1987;Potter 1988;Burger et al 1992;Buresti and Sestini 1994;Ward and Stephens 1995;West et al 1999;Ponder 2003;Famiani et al 2007;Puértolas et al 2010;Oliet and Jacobs 2007;Piñeiro et al 2013).…”
Section: Tree Shelters and Neighboring Vegetation Effects On Growthcontrasting
confidence: 68%
See 3 more Smart Citations
“…Height of N. dombeyi seedlings was not affected by the use of tree shelters neither in the xeric site, and nor in the mesic site, at least until the second growing season (prior to the browsing effect). This result contrasted with those of several hardwood (Davies 1985;Tuley 1985;Gillespie et al 1996;Bendfeldt et al 2001;McCreary and Tecklin 2001;Dorji et al 2020) and conifer species (Ward et al 2000;Jacobs 2011), which had shown a pronounced positive impact on height with the use of tree shelters. It seems that our results agree with those of the authors who indicate that the net effect of tree shelters on plant growth appeared to be site-and/or species-dependent (Frearson and Weiss 1987;Potter 1988;Burger et al 1992;Buresti and Sestini 1994;Ward and Stephens 1995;West et al 1999;Ponder 2003;Famiani et al 2007;Puértolas et al 2010;Oliet and Jacobs 2007;Piñeiro et al 2013).…”
Section: Tree Shelters and Neighboring Vegetation Effects On Growthcontrasting
confidence: 68%
“…These responses have been attributed to modified microclimatic conditions within the shelter environment (Potter 1988;Peterson et al 1994;Dupraz 1997, 2000;Clatterbuck 1999;Oliet and Jacobs 2007). Sheltered seedlings presented higher survival rates for many broadleaved and conifer species (Tuley 1985;Ward and Stephens 1995;Jacobs and Steinbeck 2001;Oliet et al 2005;Puértolas et al 2010;Valenzuela et al 2018;Dorji et al 2020). However, the effects could vary over time (Oliet et al 2005) and due to the environmental conditions of the site (Oliet and Jacobs 2007).…”
Section: Tree Shelters and Neighboring Vegetation Effects On Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…We relied on the authors’ definitions to differentiate between seedlings and saplings of the same species, acknowledging minor variations in this classification across studies. When the included studies involved multiple levels of grazing treatment (e.g., Rossetti and Begella, 2014; Dorji et al, 2020), we calculated an average where applicable. To compare the effects of livestock in different oak agroforestry systems, we categorized each case study into two groups: (1) oaks and (2) oaks with broadleaves and/or conifers.…”
Section: Methodsmentioning
confidence: 99%